Faktor-Faktor yang Berpengaruh terhadap Kinerja Karyawan PT. Universal Tunggal Logistics di Pelabuhan Tanjung Emas Semarang - Angga Bagus Kurniawan; Sulistyowati Sulistyowati; Andar Sri Sumantri (Logistics and Supply Chain Insights, 2025)
Employee performance is a crucial element in determining the success of the company's operations, especially in the logistics sector which demands efficiency and speed of service. This study aims to analyze the factors that affect the performance of employees of PT. Universal Tunggal Logistics which operates at the Port of Tanjung Emas Semarang. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to employees of the operational and administrative departments. The variables tested included work motivation, work environment, leadership style, and employee competence. Data analysis was conducted to identify the dominant factors that contribute to the performance improvement. The results of the research are expected to make an empirical contribution to the development of more effective managerial strategies in improving productivity and service quality. The novelty of this research lies in its focus on the EMKL (Sea Cargo Expedition) industry, which has unique operational characteristics compared to other service sectors, such as high dependence on cross-agency coordination, port dynamics, and tight time demands. The findings of this study are expected to be a reference for similar logistics companies in designing adaptive and evidence-based human resource policies, as well as strengthening competitiveness amid the challenges of globalization and digitalization of the logistics sector.